Decision Making Analysis Using Survey Research Methods in Islamic Education Management at SD Al-Azhar Bandung - Afriyani, Dessy; Supardi, Acep; Irawan, Irawan (AS-SABIQUN, 2023)
Islamic education is faced with various challenges and complexities in the modern context. In order to face this challenge, Islamic education management plays an important role in organizing effective educational institutions. Good management in Islamic education involves managing resources, making strategic decisions, and meeting the needs of learners and other stakeholders. The research method used by researchers is to use research with a qualitative approach. Program development. Surveys can provide valuable input in the development of better Islamic education programs. By gathering the opinions and preferences of learners, researchers can identify specific needs or interests that should be accommodated in educational programs. Identify needs and problems. Surveys can be used to identify needs and problems in the context of Islamic education. Data driven decision making. The survey provides objective and reliable data, which helps in better decision making in the management of Islamic education at SD A-Azhar Bandung. Carefully analyzed survey data can help identify trends, problems, or potential improvements that need to be prioritized. Survey research methods have high relevance in the context of Islamic education management. In an effort to improve the effectiveness of Islamic education, it is important for practitioners and researchers to make careful and sustainable use of this research method. Thus, Islamic education management can adapt and develop according to the needs of today's Muslim society.